Penguatan Branding dan Literasi Pembayaran Digital bagi UMKM - Birrur Rijaal; Ningrum Kusuma; M.Hotib Jailani; Fedrix Dewangga Amrik Julyansyah; Aufar Fadlul Hady (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Community service through a university KKN program supported the digitalization of two rural microenterprises by strengthening branding and improving digital payment literacy. The program focused on Kripik Srikandi and a local tofu producer. Activities included a rapid needs assessment, brand identity refinement (logo, packaging label, product photos, and basic social media setup), and training on the Quick Response Code Indonesian Standard (QRIS) to reduce cash dependence and increase transaction convenience. Evaluation used observation, short interviews, and a pre–post knowledge check with owners and family members involved in daily operations. Results show clearer product identity, more consistent packaging information, and improved understanding of QRIS concepts, requirements, and transaction flow. This integrated approach is feasible for short-term KKN timelines and can be replicated for similar villages to accelerate MSME readiness for the digital economy.